Comparison of Bimatoprost 0.03% and Brimonidine 0.2% in Managing Intraocular Pressure Elevation Following Nd:YAG Laser Capsulotomy for Posterior Capsule Opacification - Tulika Gupta; Rupali Kashyap; Shikhar Ganjoo (Journal of Pharmacy and Bioallied Sciences)
Background: Posterior capsule opacification (PCO) is the most common cause of vision reduction following successful cataract surgery. It is a dynamic process caused by the migration and proliferation of residual lens epithelial cells on the posterior capsule, leading to visual impairment. The standard treatment for PCO is neodymium: yttrium–aluminum–garnet (Nd: YAG) laser capsulotomy. This study aims to compare the efficacy and safety of Bimatoprost 0.03% and Brimonidine 0.2% in preventing intraocular pressure (IOP) elevation post-Nd: YAG laser capsulotomy. Materials and Methods: This study was conducted over a year at the Government Medical College, Jammu. 400 patients with PCO post extracapsular cataract extraction were randomly divided into two groups. Group A received 1 drop of Bimatoprost 0.03% and Group B received 1 drop of Brimonidine 0.2%, both administered 1 hour before Nd: YAG laser capsulotomy. Intraocular pressure was measured using Goldmann applanation tonometry before treatment and at intervals of 1 hour, 3 hours, 24 hours, 3 days, and 7 days post-treatment. Results: The mean age of patients was approximately 65 years with no significant difference between groups. The baseline IOP was similar across both groups. At 1 hour post-capsulotomy, Group A showed a mean IOP increase of 2.2 mmHg, while Group B showed an increase of 3.6 mmHg. At 24 hours, the IOP in Group A returned to baseline levels, whereas Group B still exhibited a slight elevation. No significant adverse effects were reported in either group. Conclusion: Bimatoprost 0.03% is more effective in preventing IOP elevation post Nd: YAG laser capsulotomy compared to Brimonidine 0.2%. It also demonstrated a faster return to baseline IOP levels with fewer side effects. This suggests that Bimatoprost may be a preferable prophylactic treatment for managing post-capsulotomy IOP spikes.